Clinical Spectrum and Subtype Distribution Lymphoma : A Single Center, Hospital Based Analysis - Akter, Mafruha; Khan, Mohiuddin Ahmed; Nazneen, Shahela; Haq, Qauzi Smita; Khan, Abdullah Al Zubayer (Journal of Bangladesh College of Physicians and Surgeons, 2019)
Introduction: Lymphoma is a heterogeneous group of hematological malignancy that varies in different subtypes according to geography, age, race and ethnicity. In this study, the different subtype of lymphoma according to WHO lymphoid tumor classification and clinical features of Non Hodgkins lymphoma will be analyzed and discussed at a tertiary care Hematology center. Objectives: Our aims and objective is to observe and share the single center experience of specifically Non-Hodgkin lymphoma and to contribute in formation of national lymphoma registry in future to enhance the care of potentially curable lymphomas. Materials and Method: A retrospective analysis of 226 diagnosed lymphoma cases were conducted at DMCH Hematology center from January 2016 to September 2017( total 21 months period). Data were reviewed and analyzed using simple frequency and percentage. Protocol was approved by institutional ethical review board (IRB) of DMCH. Result: The mean age of NHL is 43 ( 12-90) years with majority of patients were in 31-55 years age group and M:F is 3:1. The mean age of HL is 30 (range 4-60) years without bimodal peak observed. Mixed cellularity classical HL were found higher than nodular sclerosis HL. Majority of NHL were B cell NHL ( 86.25%) and remaining were T cell NHL (13.75%). The most common variant found was aggressive diffuse large B cell lymphoma(DLBCL) (48%), followed by peripheral T cell lymphoma PTCL (~13%) and very aggressive lymphoblastic lymphoma (LBL) (11%), low grade follicular Lymphoma (11%) and others ( ~17%). 70% NHL had nodal presentation and 30% had extra nodal involvement with GIT and CNS most commonly involved. Extra nodal presentations were more observed in DLBCL and LBL. Majority (75%) of NHL presented at advanced stage with B symptoms observed in 86% and variable IPI score. In DLBCL cell of origin was detected as non-GCB in 25(41%), GCB in 04( 6%) and unclassifiable in 03(5%) cases according to Han’s algorithm, and cell of origin was not detected in remaining cases. Conclusion: This is a small scale retrospective study, this can lead raising awareness of doing large scale national data registry for various lymphoma patients. The thorough clinical and diagnostic information about lymphoma is necessary for better management and outcome. J Bangladesh Coll Phys Surg 2020; 38(1): 23-28